A novel and efficient method for the synthesis of strong fluorescence and long afterglow BPO4 phosphors. Issue 6 (15th March 2022) - Zhu, Xingqun; Ma, Xiang; Ali, Rai Nauman; Zheng, Bo; Song, Ming
Abstract: Here, a novel method for the successful synthesis of BPO4 phosphors is reported. For this purpose, boric acid, phytic acid are served as precursor materials. Urea is used as an additive. The additive has played an important role during synthesis as it can affect the impurity residue of carbon black in BPO4 phosphors. The as-synthesized BPO4 phosphors exhibit outstanding photoluminescence properties with bright blue emission centered at 410 nm and long-afterglow luminescence phenomenon (the longest decay time can reach up to 49 s). To the best of our knowledge, we have reported the long-afterglow phenomenon of our as-synthesized BPO4 samples for the first time.